KESIAPAN GURU DALAM MEMBANGUN KARAKTER SISWA MELALUI PROYEK BERBASIS NILAI-NILAI PANCASILA - Adinda Febriza; Dewi Sulistianingsih; Nazwa Nursakinah; Jaya Adi Putra; Mutia Yulita Sari (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
Pancasila education at the elementary school level is an important foundation in shaping the nation's character. This research aims to analyze and understand more deeply the learning methods used by teachers in teaching Pancasila values at SD 115 Pekanbaru. Teachers have a great responsibility in teaching Pancasila values through formal curriculum and teaching and learning activities. However, the challenges faced by teachers are not simple, such as making learning interesting and relevant for students who tend to like learning activities that are more interactive and contextual. This research uses a qualitative paradigm with a case study research type. Data were obtained from in-depth interviews with teachers at SD 115 Pekanbaru. The results of the interviews show that the teachers have a good understanding of the values of Pancasila, including aspects of divinity, humanity, unity, populism and justice. They use diverse learning methods such as Discovery Learning, Problem-Based Learning (PBL), and group discussions to teach Pancasila values in an active and relevant manner. While these methods are relevant, their application is often constrained by time constraints and student readiness. Another challenge is the lack of a contextualized approach in learning Pancasila, making it difficult for students to connect these concepts with their daily experiences. This research also explores how to teach Pancasila values in the digital era, facing a digital generation that is more familiar with technology. The results of the analysis show that a strong understanding of Pancasila values must be balanced with the ability to connect it to students' daily lives. This research provides recommendations for teachers and school authorities to optimize more innovative and contextual learning methods, so as to improve students' understanding of Pancasila values.